Technology concept of an automated system for integration testing - Frisini, D.; Stotz, V.S.; Morlacchi, G.; Taumaturgo, V. (My University, 2022)
Looking at the trend seen in the aerospace for Verification & Validation (V&V) process, the future of integration testing will move to a more and more automated process thanks to the use of Artificial Intelligence (AI) and robotics. For the integration testing of an avionic system many different scenarios need to be executed and validated by the user running the test. Focusing on the state of the art of the integration testing, there are some issues and inefficiencies while executing the tests. Firstly, the duration of the test sets of safety-critical systems is long and involves very repetitive tasks for the operator. During this time, the system is under test and the laboratory cannot be used for other purposes which decreases the asset’s availability for other stakeholders. Moreover, with distributed offices, the on-site testing could be limitating when the execution of test procedures requires at least one person physically in the laboratory. In order to mitigate these issues ARTO (Automated Robotics for Testing Optimization) has been designed. ARTO is an automated testing system with the capability of executing functional tests that up until now are being performed by test engineers, operators or pilots. It has the objective to automate the repetitive procedures in which human interactions are required, to increase the efficiency, reduce costs and make work remotely from different locations possible. The test sequence is implemented through a dedicated HMI (human-machine interface) and executed by an automated framework, fully able to carry out the tasks needed for each sequence. The system itself consists of four main subsystems: robotics, image & audio processing, framework and user interface. ARTO is designed to be applied in the integration testing field, designed to interact, and operate with the existing testing environment of the Next-Gen Civil Tiltrotor-Technology Demonstrator. It is intended to be installed inside the Simulation and Integration Laboratory cockpit where it can operate on the displays, the keyboards, the knobs and the levers. With the video and audio feedback, it can execute the test procedures that were programmed beforehand and collect test results automatically.